From Charity to Welfare: Disability Movement, Institutional Change and Social Transformation in Post-Dictatorial Greece, 1974–81 - Vasiliki Chalaza; Christos Tsakas; Karolos Iosif Kavoulakos (Disability Studies Quarterly, 2020)
This article studies the role of the blind movement in the legislative achievements regarding the disabled people, and in the formation of blind identities and broader perceptions of disability in post-dictatorial Greece. By highlighting the institutional impact of the 1976 occupation of the Home of the Blind, this paper shows how a grassroots movement contributed to democratization, and it challenges the dichotomy between institutional and societal accounts of democratic transitions, thus touching upon themes, such as citizenship and empowerment. In doing so, this article seeks to explain the paradigm shift from charity to welfare with respect to disability as part of the broader dynamics of social transformation in Greece in the 1970s and early 1980s.
Keywords: Greek blind movement; blind identities; democratic transitions; social transformation; citizenship and empowerment